Metal uptake capacity of todorokite-type (OMS-1) and birnessite-type (OL-1) manganese oxide structures by bulk-extraction - Leonsua, Alex D. (Animo Repository, 2001)
Manganese oxide octahedral molecular sieves is a family of tunnel structures formed by corner- and edge-sharing of MnO6 octahedra. Synthetic todorokite, which has a 3 x 3 tunnel structure, is designated as OMS-1 and has a pore size of 6.9A while synthetic birnessite, which has a layer structure, and a basal spacing of 7.0A is referred to as OL-1. The presence of cations and water molecules in the channel-like pores of OMS-1 and interlayer sites of OL-1 is inherent to these structures for structural stability. In this study, the cation exchange capacity and metal uptake of OMS-1 and OL-1 are evaluated along with the elution performance and percent recovery. Analysis of the filtrate was done by AAS (atomic absorption spectroscopy) while characterization of the substrate was conducted with the use of X-ray Diffractometry (XRD), Thermal Gravimetric Analysis (TGA), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX).Percent ion exchange was computed as the relative amount of metal ions incorporated in the material per 100 parts of the total amount of metal ions in the exchanging solution. The uptake capacity of the manganese oxide materials was calculated as mmoles of metal ions absorbed in the material per gram of absorbent. Metal uptake of OL-1 (in mmoles per gram of substrate) for the various metal ions at room temperature and 24 hours stirring were: Ca 21.03, (52.53 percent ion exchange, 0.10M Ca(NO3)2) Co 2.390, (11.92 percent ion exchange, 0.050M Co(NO3)2) Hg 1.966, (98.29 percent ion exchange, 0.0050M Hg(NO3)2) and Zn 13.21, (56.18 percent ion exchange, 0.050M Zn(NO3)2). Metal uptake of OMS-1 for the various metal ions at room temperature and 24 hours stirring were: Ca 21.77, (54.88 percent ion exchange, 0.10M Ca(NO3)2) Co 0.5234, (2.610 percent ion exchange, 0.050M Co(NO3)2) Hg 1.389, (69.45 percent ion exchange, 0.005M Hg(NO3)2) and Zn 11.19, (55.27 percent ion exchange, 0.05M Zn(NO3)2). These results show that OL-1 has higher metal uptake and higher percent ion exchange than OMS-1, which has a rigid structure. Also, these results show that Ol-1 and OMS-1 are effective scavengers for heavy metal ions (Ca, Hg and Zn) except for cobalt. Elution performance and percent recovery studies show that the exchanged metal ions were still intact in the material.